Positive Emotions: Hedonistic Shopping Motivation, College Student Shopping Lifestyle - Suroso, Iwan; Rusdianto, Hutomo; Utami, Ratih Hesty (Global Health Science Group, 2022)
This study aims to examine and analyze student shopping motivation and lifestyle on positive emotions. The research design uses quantitative descriptive using primary data in the form of answers to questionnaires from respondents and then analyzed. The research sample was active students at Muria Kudus University in the Management Study Program, totaling 248 respondents. The results of the study explain that the increase in students' positive emotions for shopping using online applications (e-commerce shopee) increases because of the role of shopping motivation and because of lifestyle factors. This is due to the flexibility and speed of the vendor managing the e-commerce shoppe which is very professional, but there are research findings which explain that the negative impact is addiction to shopping through e-commerce applications making students socialize less with the environment around the campus because most activities are carried out online.